Age-related changes in false recognition: an ERP study - Robb, Lindsey (The University of Edinburgh, 2011)
Episodic memory function is well known to decline with age and there is evidence to suggest seniors prone to forget events compared to younger adults (Aizpurua & Koutstaal, 2010). What’s more, seniors are inclined to falsely ‘remember’ events which did not happen. For example, seniors are more affected by misleading post-event information (e.g. lures), remembering that information as having occurred alongside the original event (Roediger & Geraci, 2007; Chan & McDermott, 2007; Koutstaal, 2006; Aizpurua & Koutstaal, 2010). This thesis compares two hypotheses of false memory, the Cognitive Control Hypothesis and the Memory Specificity Hypothesis using an event-related potential (ERP) index of true recollection, an early left parietal old/new effect (~400 to 800ms) and adapting a paradigm used by Koutstaal (2006) which successfully demonstrated high false recognition in participants using picture stimuli. Participants undertook two explicit forced choice tasks: unintentionally studying picture stimuli by answering a size-judgment task and later a recognition test where they could answer either “old” (for repeated stimuli), “similar” (lures) or “new” (novel). Results supports previous behavioural findings by demonstrating seniors are significantly worse at discriminating between repeated and novel stimuli than younger adults, despite similar end performances with respect to repeated and novel stimuli. In addition, evidence shown here supports the suggestion that seniors are inclined to falsely “remember” events which did not happen, by misleading post-event information, compared to younger adults. An exploratory analysis of left parietal old/new effects from collected ERP data revealed unexpected conclusions. False alarms to lure stimuli (by answering “old”) showed significantly greater magnitudes compared to all other critical conditions in both age groups. This is not supported by previous research. However, younger participants showed greater correct responses to old items with greater magnitudes than correctly rejected new items which is supported by previous research. While neither hypothesis could be accepted based on the information gathered, the study design worked well and could easily be repeated. Future research replicating this study and combining it with other behavioural, ERP and fMRI results with undoubtedly yield a better understanding of the underlying processes involved cognitive ageing.
Keywords: Recognition; false memory; ERP; left parietal old/new effect